Efektifitas Model Pembelajaran CBL dalam Meningkatkan Keterampilan Berfikir Kritis Siswa di SMAN 15 Padang - Fakhra Hilali; Wirdati Wirdati (Lembaga Yasin AlSys, 2026)
Critical thinking is one of the higher-order thinking skills urgently needed in 21st-century learning, including in Islamic Religious Education (PAI). However, PAI instruction in schools remains largely teacher-centered, thus providing limited opportunities for students to develop critical thinking skills. This study aimed to analyze the effectiveness of the Case Based Learning (CBL) model in improving students’ critical thinking skills in PAI at SMA Negeri 15 Padang. A quantitative approach with a pre-experimental method was employed, with the research subjects being Grade XI students. Data were collected through a critical thinking skills test and structured observations during the implementation of CBL, then analyzed using descriptive and inferential statistics. The results showed that the application of the Case Based Learning model was effective in enhancing students’ critical thinking skills in PAI, as indicated by a test value of 0.48 and a structured observation score of 95%. The model encouraged student activeness, improved analytical abilities, and helped students connect PAI content with real-life problems. These findings confirm that Case Based Learning is a viable alternative instructional model for strengthening critical thinking skills and student engagement in PAI learning at the senior secondary level.